Uso de plantas e mix de plantas de coberturas hibernais associado ao cultivo de milho em condição de baixa altitude - Santos, Emilso Damm dos (2022)
Corn is the most produced cereal in Brazil and in the world, presenting economic and social importance. Good agronomic practices, such as the use of cover crops, enhance grain productivity and economic viability of the crop, bringing numerous benefits to it. Thus, the objective of this work was to evaluate the dry phytomass production capacity of winter cover crops, soil cover and decomposition, as well as its relationship with the agronomic performance of corn cultivation in succession in a low altitude subtropical environment. This study was conducted in Santa Maria-RS in two agricultural years 2019/2020 and 2021/2022. The experimental design used was randomized blocks, with 10 treatments and 4 replications, totaling 40 experimental units. The experiment was carried out with four winter cover crops, being white oat, black oat, forage radish and vetch in their own cultivation and in the form of a mix of cover crops. Where during the development period, the soil cover was measured using the NDVI system, after the full flowering/grain filling period, the dry matter phytomass production was measured. And later the decomposition curves of the treatments of cover crops. After the area was desiccated, sowing was carried out at reduced spacing of 0,5 m between rows and population adjusted to 70000 plants ha-1 of the single hybrid DKB290, to evaluate the agronomic performance of corn. Where the fertilization followed the recommendations for the culture according to soil analysis, and the technical indications for the maize crop were followed for the other crop managements. Therefore, in a low-altitude subtropical environment, AP and AB treatments showed greater maintenance of dry phytomass in soil cover at the end of the 150-day period, with values greater than 40% of the initial volume of dry phytomass delivered to the soil, in crops with occurrence of the La Niña phenomenon. For the total production of dry phytomass, treatments NB and AP+NB+EC stand out, which present averages above 4000.00 kg ha-1 , although they do not differ statistically from other treatments. For grain yield, in years with La Niña behavior in the critical periods of flowering and grain filling, there was no difference between plants and cover crop mix in both years. There were differences in the statistical response for the different productive components evaluated, in the different years of study. There were positive correlations between EC, DE and MMG grain yields in both crop years. CE also showed a high positive correlation with DE and, due to its easy measurement, it can be adopted as a character for indirect selection in years with La Niña behavior. The importance of using cover crops in the winter period is highlighted, since the average of the experiment was 2559 kg ha- ¹ higher than the state average in the year 2019/20 and 3694 kg ha- ¹ in the year 2021/22.